2021
DOI: 10.1177/17531934211054282
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of clinical assessment of distal radioulnar joint instability

Abstract: Accurate assessment of distal radioulnar joint (DRUJ) stability is increasingly recognized as an important part of clinical examination of the wrist. The ability of 30 specialist UK hand surgeons to clinically determine the stability of four volunteers’ wrists was assessed. Volunteers’ wrist stability had previously been confirmed with a validated measurement rig. Use of the wrist ballottement test as the primary examination technique yielded a positive predictive value of 81%, a negative predictive value of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Previous studies on upper extremity conditions, such as SLD or proximal humeral fractures, have already noted limited reliability and reproducibility of diagnostic tests (Bakker et al., 2022; Papakonstantinou et al., 2016). A recent study on the reliability of the ballottement test reported a low sensitivity of 24% and concluded the test could be unreliable (Pickering et al., 2022). In our study, the ballottement test was carried out during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on upper extremity conditions, such as SLD or proximal humeral fractures, have already noted limited reliability and reproducibility of diagnostic tests (Bakker et al., 2022; Papakonstantinou et al., 2016). A recent study on the reliability of the ballottement test reported a low sensitivity of 24% and concluded the test could be unreliable (Pickering et al., 2022). In our study, the ballottement test was carried out during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are case series recommending acute TFCC repair, but we do not see many patients with long-term symptomatic DRUJ instability requiring treatment after distal radial fractures despite these fractures being very common. It should be noted that Pickering et al. (2022) have shown that clinical assessment of DRUJ instability is unreliable, so any published studies on DRUJ instability based purely on clinical testing pre- or post-intervention remain open to question.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Various published studies have reviewed DRUJ instability and reported ulnar-sided surgery at the same time as stabilization of the distal radial fracture to address DRUJ instability (Kasapinova and Kamiloski, 2019). As it has been shown that clinical assessment of DRUJ instability is unreliable (Pickering et al., 2022) and we know all patients with distal radial fractures have DRUJ instability (Giddins and Pickering, 2021), the published studies advocating ulnar-sided treatment have to be viewed sceptically. Currently there is no evidence that additional ulnar-sided wrist surgery at the same time as stabilization of the distal radial fracture improves patient outcomes.…”
Section: Specific Druj Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Clinical detection of subtle DRUJ laxity may be difficult and not reliably detected clinically. 12 Ulnar wrist pain may be the only symptom in these patients, making the diagnosis of a foveal injury less straightforward. Furthermore, foveal tears may occur with injury to another component of the TFCC.…”
Section: Introductionmentioning
confidence: 99%